Effect of Financial Literacy, Financial Attitude, and Lifestyle on Financial Management (Study on Students in Bandar Lampung City) - Intan Nursalma; Ridwansyah Ridwansyah; Wahyu Iryana (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of financial literacy, financial attitudes, and lifestyle on the financial management of students in the city of Bandar Lampung. Good financial management is crucial in creating personal economic stability, especially for students who are in the process of becoming financially independent. This study uses a quantitative approach to the survey method by distributing questionnaires to 150 respondents selected through a simple random sampling technique. Data analysis was done using multiple linear regression with the help of the SPSS version 29 program. The results showed that financial literacy, financial attitudes, and lifestyle have a positive and significant effect on Student Financial Management. These findings are in line with the framework of the Theory of Planned Behavior. This study recommends improving financial literacy and strengthening more planned attitudes and lifestyles as effective strategies in encouraging healthy financial management behavior among students.